The impact of depression and anxiety on pain reported by patients with rheumatoid arthritis undergoing treatment - Nicole Rodrigues de Magalhães; Vitória Novaes Figueiredo Daleaste; Marielle Bernardi Gomes; Marcia Midori Shinzato (Acta Scientiarum. Health Sciences, 2023)
This study analyzed the joint pain of 46 patients with rheumatoid arthritis (RA) undergoing treatment with disease-modifying antirheumatic drugs (DMARD), for at least one year, and evaluated by pain intensity numeric scale and by the McGill Pain Questionnaire (MPQ), anxiety and depression by the Hospital Anxiety and Depression Scale (HADS). We compared them with 46 patients without RA matched by age and sex. We also examined the relationships between anxiety and depression and pain intensity, disease activity and physical dysfunction accessed by the Rheumatoid Arthritis Disease Activity Index (RADAI) and the Health Assessment Questionnaire (HAQ), respectively. Most patients with RA, 93.5%, continued to report joint pain and had higher pain intensity and higher scores in all domains of the McGill Pain Questionnaire (MPQ) than 58.7% of the 46patients without RA with joint pain. Patients with RA were more likely to have depression defined by HADS≥11 than the controls but the association was non-significant when adjusted for the presence of pain. The median score of anxiety symptoms was significantly higher in patients with RA than in those without RA. There was an association of depression and a positive significant correlation of anxiety symptoms with higher intensity of pain, disease activity and physical dysfunction. There was no difference between patients with RA and depression and without depression on the sensory domain and in the total MPQ score. Otherwise, there was a moderate significant correlation of the levels of anxiety with all pain domains of the MPQ, except the sensory one. In conclusion, pain remains a prevalent symptom in RA patients despite treatment. More studies are necessary to verify if the qualitative assessment of pain could be used to evaluate the influence of anxiety and depression on pain reported by these patients.